Evaluation of anti-inflammatory activity of ethanolic extract of Derris brevipes (benth.) Baker leaves - Nesni M Makkar,; Veena R,; Sancy Mary Sam,; Jeena Ann John,; Kuriachan, Sanitha (Asian Journal of Medical Sciences, 2023)
Background: Ethnopharmacological relevance: Derris brevipes (benth.) Baker is widely used as an anti-arthritic agent in traditional medicine. Aims and Objectives: This study evaluated the anti-inflammatory activity of ethanolic extract of D. brevipes (EEDB) leaves, a member of the Leguminosae family in vitro and ex vivo. Materials and Methods: The EEDB leaves of was screened for anti-inflammatory activities by protein denaturation analysis and proteinase inhibition analysis. Prednisolone was used as the standard. EEDB (at doses of 300 mg/kg and 600 mg/kg) was administered through the oral route. Ex vivo analysis was performed by estimating the expression of tumor necrosis factor-alpha (TNF-α) in collagen (chicken sternal collagen)-induced arthritis (CIA) in Sprague–Dawley rats using the reverse transcription polymerase chain reaction method. The data were analyzed using one-way analysis of variance, followed by Dunnet’s multiple comparison tests. Results: Prednisolone (100 mcg/mL) and EEDB (600 mcg/mL) showed percentage inhibition of 80.32% and 80.04%, respectively, in protein denaturation assay. Similarly, prednisolone (600 mcg/mL) and EEDB (600 mcg/mL) showed 66.03% and 56.69% inhibition in the proteinase activity. Synovial tissue TNF-α levels showed a significant decrease in EEDB-treated groups and prednisolone-treated group compared to CIA control rats. Conclusion: From this study, it was concluded that the D. brevipes leaf extract possesses anti-inflammatory activity, which explains its beneficial role in rheumatoid arthritis.